Proposal to Distribute Remaining Windfall Gold Sales Profits and Strategy to Make the Poverty Reduction and Growth Trust Sustainable. (Policy Papers; Policy Paper, 2012)
This paper revisits the use of the remaining gold sales windfall profits (SDR 1.75 billion). Directors previously considered three main options: using them as part of a strategy to boost the capacity of the PRGT; counting them towards precautionary balances; or investing them in the Investment Account's endowment. In past discussions, Directors expressed a wide range of views on these options, and the resources have continued to be held in the Investment Account pending a decision by the Executive Board.